Assessment of performance and challenges of small and micro enterprises: Fireweyni town, Ethiopia - Tuem Gebre Abraha; Haftom Teshale Gebre (PLoS ONE, 2025)
Micro and small enterprises are crucial drivers of economic growth, job creation, and poverty reduction in developing countries. Recognizing this, Ethiopia has implemented measures to enhance the operation of micro and small enterprises. However, many micro and small enterprises in the country face significant challenges and exhibit deteriorating performance, with limited progression from one enterprise level to the next. This study aims to assess the performance and challenges of micro and small enterprises in Fireweyni town. Employing a mixed-methods approach, the study integrates both qualitative and quantitative research. Primary data were collected using a structured questionnaire. A probability sampling technique, combining convenience and stratified random sampling, was applied to a sample of 373 micro and small enterprises in Fireweyni town. The study is descriptive and cross-sectional, focusing on the performance of MSEs and the obstacles they encounter. Data collection included responses from 5483 micro and small enterprise operators, distributed across service (853), manufacturing (341), urban agriculture (1073), construction (155), and trade (3061) sectors. The data were analyzed using descriptive and inferential statistical methods, with the aid of the Statistical Package for Social Sciences (SPSS) version 20 and STATA version 16. Results of the study revealed that, every variable (factor) incorporated in this study was statistically significant, impacting the performance of SMEs and businesses within the study area. The Pearson correlation coefficient test results showed that all independent variables have a significant relationship with MSE business performance. The study’s conclusions indicate that financial control, marketing strategy, managerial expertise, government regulations, and business information services significantly affect the performance of small and micro businesses in Fireweyni town.